Pendampingan Recyle Limbah Pengolahan Kayu Pada UMKM “Kayu Kreatif”, Kecamatan Setu Kabupaten Bekasi - Untari, Dhian Tyas; Khasanah, Fata Nidaul; Anjani, Allisya Andrea; Putri, Amelia (Jurnal Pengabdian kepada Masyarakat UBJ, 2022)
A small industry has a close relationship with the existence of human resources as the driving force of the small industry itself. SME "Kayu Kreatif" is engaged in wood processing which so far has only been limited to door and window frame products. The rest of the wood that is not used is finally just wasted without being used. Aspects of problems with partners related to production aspects and aspects of logo and brand management. The problems and solutions that will be raised are: 1). Wood waste has not been utilized which then only becomes waste and causes further problems so that the solution that will be given is assistance in making cellphone holder craft products with wood waste materials and 2). Products that have been made need to be branded and patented so that in marketing they will have a strong product. The solution that will be given is to create a logo and brand to prepare the product to be marketed.